당뇨 여성의 성기능과 삶의 질의 관계 - 진동순 (The Graduate School, Ajou University, 2006)
본 연구는 당뇨여성의 성기능 정도를 조사하고 성기능과 삶의 질의 관계를 분석하여 당뇨여성의 삶의 질을 높일 수 있는 간호중재의 기초 자료를 제공하고자 2006년 4월27일- 5월 22일까지 경기도내 A대학병원과 S대학병원의 외래 환자 70명을 대상으로 설문지를 통해 자료를 수집하였다. 연구도구로는 Taylor 등(1994)이 개발한 성기능 측정도구인 BISF-W와 Dunbar(1992)등이 개발한 삶의 질 척도(Smithkline Beecham'Quality of life' scale)를 윤진상 등(1998)이 수정하여 한국판으로 표준화 한 삶의 질 측정 도구를 사용하였다. 수집된 자료는 SPSS 12.0을 이용하여 서술통계, t-test, x²-test, one way ANOVA, Pearson correalation등으로 분석하였으며 결과는 다음과 같다. 1. 대상자의 성기능장애 정도를 유형 별로 조사한 결과 성 욕구장애 정도는 ꡒ성적인 생각이나 환상이 없었다ꡓ가 61.4%, ꡒ성행위를 하고 싶은 욕구가 없었다가ꡓ 54.3%로 나타났고, ꡒ성행위 시작 시도는 ꡓ남편이 먼저 요구한다가 72.9%로 나타났고, ꡒ남편의 성적 시도에 대한 반응ꡓ에서 대부분 거절한다가 65.7%로 나타났으며, ꡒ얼마나 자주 성행위를 하였는가ꡓ는 원하는 만큼이 58.6%로 나타났다. 성 각성 장애 정도는ꡒ성적 경험을 통한 성적 흥분을 전혀 느끼지 못했다ꡓ가 24.3%이었고,ꡒ성적 흥분의 억압을 받았다가ꡓ 30.%로 나타났다. 극치감 장애 정도에서는25.7%가 ꡒ전혀 느끼지 못했다ꡓ로 나타났다. 성교 통증 장애 정도에서는 ꡒ질 윤활액 결핍이 있다ꡓ가 70.0%, ꡒ성교 후 통증이 있었다ꡓ가 27.1%, ꡒ성교 후 두통이 있었다ꡓ가 10.0%로 나타났고, ꡒ성교 후 질감염이 있었다ꡓ가 10.0%로 나타났다. 2. 성기능 관련 특성에 대한 인지정도 에서는ꡒ당뇨로 인한 건강 상태가 성생활에 영향을 주었는가ꡓ에 대해 58.9%가 영향을 주었다고, 응답하였고,ꡒ성적욕구를 남편에게 편하게 이야기 할 수 있는가ꡓ에 대해서는 27.1%가 말을 못했다고 하였다. ꡒ성생활에 대한 만족의 변화는 있는가ꡓ에 대해서는 30.0%가 감소했다 로 응답하였고, ꡒ남편과의 성적인 관계에 대해서ꡓ는 불만족이 37.1%로 나타났다.ꡒ외모에 대해서는ꡓ불만족이 35.7%로 나타났고, ꡒ삶에 있어 성생활의 중요성ꡓ은 22.9%가 중요하지 않은 것으로 인지하고 있었다. 3. 대상자의 인구사회학적, 건강관련, 질병관련 특성에 따른 성기능장애 에 대한 차이검정에서는 폐경유무(p<.002)와 연령(p<.023)에서만 유의한 차이가 있는 것으로 나타났다 4. 대상자의 삶의 질 총점은 최대 230점에 평균 118.00으로, 중간보다 약간 높았다. 영역별로는 활력이 가장 높았고, 신체적 안녕이 가장 낮았다. 5. 성기능과 삶의 질 간의 상관관계를 분석한 결과 성기능 장애 정도와 삶의 질 간에는 유의한 상관관계가 없는 것으로 나타났다. 결론적으로, 당뇨여성의 성기능 장애정도가 높다는 사실과 특히, 당뇨여성의 대다수가 질 윤활액 결핍, 성욕 감소, 극치감 감소, 성교통증 등으로 인해 만족스런 성생활을 하지 못하고 있다는 것을 파악하였다. 그러나 삶의 질에 있어서는 일반여성과 당뇨여성에서 삶의 질을 인지하는 정도에 차이가 없었다. 여성의 성기능은 개인차가 크고, 다양하므로 당뇨여성의 성기능 장애를 예방 또는 완화 시킬 수 있는 중재 방안으로 삶의 질 증진 및 개선을 위한 성상담 및 교육 프로그램 개발이 중요함을 강조하고자 한다 핵심어 : 당뇨여성, 성기능, 삶의 질 The purpose of this study was to investigate the level sexuality of diabetic women, and analized relations between sexuality and quality of life in diabetic women, provide basic data contributed in nursing intervention. A convenience sample consisted of 70 subjects with diabetes who attended outpatient department of A university hospital and C university hospital in S city. After verbal consent was obtained, subjects were asked to complete a questionnaire including BISF-W (Brief Index Sexuality Function-Women) developed by Taylor et. al(1994) and Smithkline Beecham's 'Quality of life' scale. Data were collected from April 27 to May 22, 2006. The data collected were analyzed by descriptive statistics, t-test, x²-test, one way ANOVA, Pearson correalation using SPSS 12.0 program. 1. The survey results on the degree of sexual dysfunction of the subjects by type of dysfunction are as follows: Concerning the degree of sexual desire disorder, 61.4% of the subjects responded that they had "no sexual thought or fantasy", and 54.3% responded that they had "no desire for sexual intercourse." To the question on "Who first demanded sexual intercourse?", 72.9% responded that their husband did. To the question "What was your response to your husband's demand for sexual intercourse?", 65.7% responded that they mostly rejected it. To the question "How often did you have sexual intercourse?", 58.6% responded that they had it as often as they wanted. For the degree of sexual arousal disorder, 24.3% responded that they "did not feel sexual arousal at all from their sexual experience" and 30,0% responded that they "felt a suppression of sexual arousal." With regard to the degree of orgasmic disorder, 25.7% responded that they felt no orgasm at all. Concerning the degree of sexual pain disorder, 70.0% had "a lack of vaginal lubrication", 27.1% "a pain after sexual intercourse," 10.0% a headache after sexual intercourse, and 10.0% a vaginal infection after sexual intercourse. 2. The survey results on the subjects' recognition of the characteristics of sexual function were as follows: To the question "Did your health condition, i.e. diabetes affected your sex life," 58.9% responded that it did. To the question "Can you openly talk about sexual life with your husband?", 27.1% responded that they could not. To the question "Is there any change in your satisfaction on your sex life?", 30.0% responded that it decreased. To the question on their satisfaction on their sexual relationship with their husband, 37.1% were not satisfied. To the question on their satisfaction on "their looks," 35.7% were not satisfied. To the question "How important sexual intercourse is in your life?", 22.9% responded that it was not important. 3. The test of differences in sexual dysfunction according to demographic, health- and disease-related characteristics revealed that significant differences existed only with regard to menopause (p<.002) and age (p<.023). 4. The average score of the quality of life for the subjects was 118.00 against the highest score of 230, which was a little higher than the middle level. According to area, the score for vitality was the highest while that for physical well-being was the lowest. 5. From the analysis of the correlations between sexual function and the quality of life, no significant correlations were found between the degree of sexual dysfunction and the quality of life. In conclusion, this study discovered that the degree of sexual dysfunction of women with diabetes was high, and in particular that most of the women with diabetes did not have satisfactory sex life because of lack of vaginal lubrication, lower sexual desire, lower orgasm, and sexual pain. However, there was no difference in the recognition on the quality of life between normal and diabetic women. As the sexual function of women varies widely among individuals, we would like to emphasize the importance of sexual counselling and education programs to improve the quality of life of diabetic women to prevent or relieve their sexual dysfunction.
학위논문(석사)--아주대학교 일반대학원 :간호학과,2006. 2
Keywords: 당뇨여성; 성기능; 삶의질